CORRELATION BETWEEN THE USE OF GAMES AND STUDENTS’ MOTIVATION IN LEARNING ENGLISH - MUKMIN MUKMIN; YUSNIATI N SABATA (JURNAL PENDIDIKAN GLASSER, 2017)
This research aims at analyzing correlation between the use of games and students’ motivation. Quantitative method with correlation research design was used in this research. Its population consists of 65 students taken as research sample. Total sampling technique was applied in this research. Two independent variables correlated were the use of games as variable X and students’ motivation as variable Y. Questionnaires used to collect data consisted of 40 items, in which 20 items related to the use of games and another 20 items concerning with students’ motivation. The data were analyzed by applying computer program of SPSS (statistical package for social science) 18. Findings of the research indicate that the coefficient correlation (rxy) is 0.571, with the degree of freedom df = N-2 and the level of significance 0.05 or 5%. Value of r-table 0.244 indicates that the value of rxyis higher than rt (0.571 > 0.244). Thereby, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected, so there is a significant correlation between the implementation of games and motivation of students at second semester of grade VIII. It means that the more often teachers use games the higher students motivation in learning English. Keywords: Correlation, games, and Motivation